Study of board bending degree on hydrodynamic performances of a single-layer cambered otter-board - Wang Lei; Wang Lu Min; Liu Yong Li; Yu Wen Wen; Qi Guang Rui; Wang Yong Jin; Zhang Xun; Zhang Rong Jun (E3S Web of Conferences, 2019)
The effect of board bending degree on hydrodynamic performances of a single-layer cambered otter-board was investigated using engineering models in a wind tunnel. Three different bending degree boards were evaluated at a wind speed of 28 m/s. Parameters measured included: drag coefficient Cx, lift coefficient Cy, pitch moment coefficient Cm, center of pressure coefficient Cp , over a range of angle of attack (0° to 70°). These coefficients were used in analyzing the differences in the performance among the three otter-board models. Results showed that the bending of the board(No. 2, No. 3) increased the water resistance of the otter-board, and improved the lift coefficient of the otter-board in the small angle of attack (0°<α≤20 °) ; the maximum lift coefficients Cy of otter-board model (No. 1) was higher (1.680, α = 25°). the maximum lift–drag ratios of models (No. 1, No. 2 and No. 3) are 6.822 (α = 7.5 °), 6.533 (α = 2.5 °) and 6.384 (α = 5.0°), which showed that the board bending reduces the lift-to-drag ratio of the otter-board.The stability of the No. 3 model was better than those two models (No. 1, No. 2) in most range of attack angle, but No. 1 otter-board model had a better stability in roll of otter-board. The findings of this study can offer useful reference data for the structural optimization of otter-boards for trawling.